DETERMINANTS OF THE USE OF CHILD LABOUR IN CROP PRODUCTION IN ESTAKO WEST LOCAL GOVERNMENT AREA OF EDO STATE, NIGERIA. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The apparition of small children labouring long hours under inhumane conditions has led to an intense debate concerning child labour over the past decade and a half, mostly centering on its role in agricultural productivity.  This study therefore explored into the determinants of the use of child labour in crop production in Estako West local government area of Edo state.  A multistage random sampling technique was used in the sample selection process.  Six (6) communities were randomly selected from which seventeen (17) respondents were randomly selected from each of the six communities, making a total of one hundred and two (102) respondents. Data obtained were analyzed using descriptive statistics and inferential statistics.  The results showed that 61.8% of the respondents were between the ages of 11 and 14 years with the mean age of 14 years.  52.9% of the children were males, while 47.1% were females, all (100%) were single, 31.4% of the children were in JSS, 82.5% were involved in planting and 81.4% were involved in weeding. The regression results indicated a R2 value of 0.893 which implies that 89.3% of the variability in man hours of child labour (Y) is being accommodated by the independent variables (Xs) specified in the model, with household (X3) and experience (X4) significant at 5% level. This indicated X3 and X4 are important variables that influence the use of child labor on the farm.  Government and non-governmental organizations should make subsidized loans available to local farmers to aid them financially in their crop productions.